Metrics That Matter: Counting What's Really Important to College Students - Christopher Muellerleile (Metrics That Matter: Counting What's Really Important to College Students, 2023)
Colleges sell themselves by the numbers—rankings, returns on investments, and top-ten lists—but these often mislead prospective students. What numbers should they really be paying attention to?High school and college students are inundated by indicators and rankings supposedly designed to help them decide where to go to college and what to study once they arrive. In Metrics That Matter, coauthors Zachary Bleemer, Mukul Kumar, Aashish Mehta, Chris Muellerleile, and Christopher Newfield take a critical look at these metrics and find that many of the most popular ones are confusing, misleading, and—most importantly—easily replaceable by more helpful alternatives.